THE EFFECT OF VENTILATION AND OCCUPANT ACTIVITIES TOWARDS INDOOR AIR QUALITY IN RESIDENTAL HOUSE FOR FINE PARTICULATE - Syafei, Arie Dipareza; Herumurti, Welly; Nabila, Dessy Farihi; Arisani, Nabila (Purifikasi, 2024)
Indoor air quality is important because it is related to human health. One of the factors that can affect indoor air quality is ventilation and occupant activities. Poor air quality can cause respiratory problems and sick building syndrome. One of the harmful pollutants that affects human health is PM2.5. This study aims to evaluate the quality of PM2.5 within indoor air against quality standards and determine the ventilation and occupant activities that affect the concentration of PM2.5. Primary data sources were obtained by measurements and questionnaires. Eleven houses (11) were sampled on 2 weekdays and 1 weekend. PM2.5 concentration measurements were carried out indoors and outdoors. The method in this study uses multiple linear regression analysis through the SPSS application. The concentration of PM2.5 indoors and outdoors has a moderate to strong correlation due to window opening activities. Fan usage time has a significant effect on reducing the concentration of fine particulates. The amount of furniture is also one of the factors that increase the concentration of fine particulates. The activity of opening a window has two effects, it can increase or decrease concentration. Further research is needed to observe the window opening to confirm the results of this study.